Curriculum of Love and Religious Moderation in Madrasah Learning: Strategy for Building a Generation with Humanistic and Tolerant Character - Aslinda, Aslinda; Amrizon, Amrizon (Edupedia Publisher, 2025)
This study aims to explore the implementation of the curriculum of love and religious moderation in madrasah learning and assess its impact on the learning climate and students’ character development. Using a descriptive qualitative approach and a case study method, the research was conducted at MTsN 2 Tanah Datar, involving teachers, school principals, and students as subjects. Data collection techniques included in-depth interviews, participatory observation, and document analysis of teaching tools. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, employing techniques and source triangulation to ensure validity. A hermeneutic approach was applied to capture the deeper meaning of participants' experiences in implementing values of love and moderation. The findings indicate that this curriculum fosters a more harmonious classroom climate, increases student engagement, and cultivates discipline and responsibility. In conclusion, the curriculum of love and religious moderation proves effective in shaping a conducive learning environment and developing students’ humanistic and tolerant character. It is recommended for broader implementation in madrasahs, accompanied by teacher training and value-based curriculum evaluation to ensure sustainability and relevance.